PARTISIPASI PEDAGANG DALAM PELAKSANAAN KEBERSIHAN, KETERTIBAN DAN KEINDAHAN DI PASAR PAGI ARENGKA PEKANBARU - Aperta, Rizky; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine or describe the participation of the traders at Pasar Pagi Arengka Pekanbaru in creating hygiene environmental market and describe the factors that influence participation of traders at pasar Pagi Arengka Pekanbaru. Informants are formal leaders and informal leaders. The head of the Sanitation Department, Parks and Cemeteries Pekanbaru, while the informal leaders are vendors and janitors who are knowledgeable about research problems. Analyze data using descriptive method by formulating, decipher and interpret based on a theoretical basis that are closely related to the concerns expressed. The study states that the mechanism set up merchant participation in waste management in the Pasar Pagi Arengka Pekanbaru starting from the planning phase, implementation phase, namely the socialization of the form of regulation of waste management. The next stage of supervision and control is the maintenance and improvement of public discipline, the manager made a report, to be submitted to the government and the public according to the rules or agreed mechanism. Factors that influence the shape and level of participation traders in waste management in the Pasar Pagi Arengka Pekanbaru which could be seen from the type of work because of factors influence the degree of activity in the group and individual mobility. The duration of trade has strong links with the form of public participation in the process of involvement of traders in physical activities / community service. The longer a person lives, settle and trade in the region in general will be a positive influence on the development of psychological life. In this case the greater number of neighbors known, the higher the psychological bond with the environment that affect the magnitude of the desire for, has engaged in joint activities.Keywords: Participation, Traders, Cleanliness, Orderliness, Market